PIGEON PARAMYXOVIRUS IN WILD AVIFAUNA OF KAZAKHSTAN - Karamendin , K.O.; Kydyrmanov , A.I.; Kasymbekov , E.T.; Daulbayeva , K.D.; Khan , E.Y.; Sayatov , M.K. (Eurasian Journal of Applied Biotechnology, 2018)
Field materials such as cloacal and tracheal swabs were collected from aquatic and terrestrial birds at the ornithological station Shakpak (Jambyl region) in 2014 and 2016. Twenty-three samples were obtained from two species of Columbiformes: the rock dove and the rufous turtle dove. Positive samples were found in eleven of the twelve samples obtained from the rock dove, while samples from the rufous turtle dove were negative. The article describes the comparative molecular-genetic and phylogenetic properties of velogenic Newcastle disease virus (NDV) strains isolated in southern Kazakhstan. To determine the pathotype of the Kazakhstan isolates from wild birds, the gene encoding the fusion protein was sequenced. The proteolytic cleavage site was defined as RRQKR*F, which corresponds to a velogenic/mesogenic serotype. The partial F gene-based sequence analysis revealed an evolutionary relationship to sub-genotype VIb formed by strains isolated in geographically close regions — south of western Siberia and Altai, and also to a virus that had previously circulated in southeast Kazakhstan. Investigations conducted in this field allow for the identification of regions in Kazakhstan that are susceptible to NDV outbreaks. The findings will also enhance our knowledge of circulating PPMV strains in Kazakhstan. Extensive environmental and epizootological studies of PPMV are of particular importance for the safety of local poultry farming.